2006
DOI: 10.1091/mbc.e05-07-0698
|View full text |Cite
|
Sign up to set email alerts
|

The CNA1 Histone of the CiliateTetrahymena thermophilaIs Essential for Chromosome Segregation in the Germline Micronucleus

Abstract: Ciliated protozoans present several features of chromosome segregation that are unique among eukaryotes, including their maintenance of two nuclei: a germline micronucleus, which undergoes conventional mitosis and meiosis, and a somatic macronucleus that divides by an amitotic process. To study ciliate chromosome segregation, we have identified the centromeric histone gene in the Tetrahymena thermophila genome (CNA1). CNA1p specifically localizes to peripheral centromeres in the micronucleus but is absent in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 85 publications
5
65
2
Order By: Relevance
“…Some of the results described here confirm or extend the studies reported by Cervantes et al (6), while others differ. We also studied additional properties of Cna1p.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Some of the results described here confirm or extend the studies reported by Cervantes et al (6), while others differ. We also studied additional properties of Cna1p.…”
Section: Discussionsupporting
confidence: 90%
“…Both our results and those of Cervantes et al (6) indicate that Cna1p is a chimeric histone with a H3-like histone fold domain, similar to the CenH3s of other organisms. The micronuclear-specific localization of Cna1p-GFP in small dots whose number correlates closely with the number of micronuclear chromosomes and whose behavior during mitosis is as expected for centromeres argues strongly that Cna1p is the centromeric H3 in Tetrahymena.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The macronucleus differs from other eukaryotic nuclei in several respects. It is derived from the micronucleus during conjugation through elaborate genomic rearrangement of the five germ line chromosomes into more than 200 chromosome fragments ranging in size from 20 to more than 3,000 kb (for a review, see reference 52) that have telomeres but no centromeres (7). During vegetative growth, the macronucleus divides by an amitotic mechanism that remains ill defined.…”
mentioning
confidence: 99%